Effects of Hydrotherapy Programmes on Knee Osteoarthritis - Adriza Gogoia; Anoushka Saikia; Prasenjit Bhattacharyya (International Journal of Orthopedic Nursing and Practices, 2025)
Osteoarthritis (OA) of the knee is a progressive degenerative disorder characterized by the breakdown of articular cartilage, joint margins, and surrounding structures. It is one of the most common musculoskeletal conditions affecting weight-bearing joints, leading to functional limitation, pain, stiffness, and reduced quality of life. Although OA is irreversible, early intervention and appropriate therapeutic strategies can slow its progression and help delay invasive procedures such as total joint replacement. Hydrotherapy has gained recognition as an effective, low-impact therapeutic approach that utilizes the physical properties of water—including buoyancy, viscosity, and thermal effects—to reduce joint load, improve mobility, and enhance muscle strength. These water-based programmes may provide a safer alternative for individuals who struggle with land-based exercises due to pain or mobility restrictions. This study aims to explore the effects of hydrotherapy programmes on individuals with knee osteoarthritis, emphasizing improvements in pain reduction, range of motion, functional mobility, gait patterns, and overall joint health. The intervention leverages warm-water environments to reduce gravitational stress, support movement, and facilitate controlled exercise. By examining patient outcomes, this research highlights hydrotherapy’s potential to alleviate symptoms, improve quality of life, and slow disease progression. Understanding its benefits may help clinicians integrate aquatic therapy more effectively into OA management protocols.
Keywords: Hydrotherapy; aquatic therapy; joint mobility; knee osteoarthritis; pain reduction